PSYCHOLOGICAL CONTRACTS, INNOVATIVE WORK BEHAVIOR, AND KNOWLEDGE SHARING INTENTION: THE ROLE OF WORK ENGAGEMENT AND JOB RESOURCES - Sulistiawan, Jovi; Andyani, Damaresty (Jurnal Aplikasi Manajemen, 2020)
This study examines the relationship between the psychological contract and innovative work behavior. The psychological contract consists of two types, relational and transactional. We tested whether work engagement mediates the relationship between those two types of psychological contract and innovative work behavior and knowledge sharing intention. Besides, we also tested the moderating effect of job resources whether to strengthen or weakened the relationship between psychological contract and work engagement. Using transformational directorate employees as our respondents because they are demanded to work innovatively. We employed Partial Least Square to test the hypotheses. Our findings will be discussed in the results and discussion section and followed by the implication of this study. This study contributes to understanding how and when the types of psychological contracts lead to innovative work behavior and knowledge sharing intention through work engagement.